TRANSLATING POETRY ON E-LEARNING DISCUSSION FORUM; STUDENTS’ LEXICAL CHOICES AND CULTURAL ORIENTATIONS - Afriliani Afriliani (British : Jurnal Bahasa dan Sastra Inggris, 2022)
AbstractTranslating poetry in the distance learning ecosystem provides students the opportunity to learn through an online discussion forum called E-Learning. Students are given the task of translating poetry and leaving comments on the work of other students. This article compares three translations of the poem entitled "Air Mata Bunda". From the results of the translation, it was found that students had variations in the structure, procedural tendencies and ideology of translation poetry of Source Language (SL) to target language (TL). Word choice, aesthetic considerations, and cultural substitutions that are reflected in the translation can all cause variations in the translation. The researcher also discovered that there was still a low degree of engagement in e-learning, which encouraged the creation of a better framework for discussion, particularly when it came to practicing text translation. Keywords: translation, poetry, cultural substitution, and E-Learning